Recurrent NCOA2 gene rearrangements in congenital/infantile spindle cell rhabdomyosarcoma1. Issue 6 (5th March 2013) - Mosquera, Juan Miguel; Sboner, Andrea; Zhang, Lei; Kitabayashi, Naoki; Chen, Chun‐Liang; Sung, Yun Shao; Wexler, Leonard H.; LaQuaglia, Michael P.; Edelman, Morris; Sreekantaiah, Chandrika; Rubin, Mark A.; Antonescu, Cristina R.
Abstract Spindle cell rhabdomyosarcoma (RMS) is a rare form of RMS with different clinical characteristics between children and adult patients. Its genetic hallmark remains unknown and it remains debatable if there is pathogenetic relationship between the spindle cell and the so‐called sclerosing RMS. We studied two pediatric and one adult spindle cell RMS by next generation RNA sequencing and FusionSeq data analysis to detect novel fusions. An SRF‐NCOA2 fusion was detected in a spindle cell RMS from the posterior neck in a 7‐month‐old child. The fusion matched the tumor karyotype and was confirmed by FISH and RT‐PCR, which showed fusion of SRF exon 6 to NCOA2 exon 12. Additional 14 spindle cell (from 8 children and 6 adults) and 4 sclerosing (from 2 children and 2 adults) RMS were tested by FISH for the presence of abnormalities in NCOA2, SRF, as well as for PAX3 and NCOA1. NCOA2 rearrangements were found in two additional spindle cell RMS from a 3‐month‐old and a 4‐week‐old child. In the latter tumor, TEAD1 was identified by rapid amplification of cDNA ends (RACE) to be the NCOA2 gene fusion partner. None of the adult tumors were positive for NCOA2 rearrangement. Despite similar histomorphology in adults and young children, these results suggest that spindle cell RMS is a heterogeneous disease genetically as well as clinically. Our findings also support a relationship between NCOA2‐rearranged spindle cell RMS occurring in young childhood and the so‐called congenital RMS, which often displays rearrangements at 8q13 locus (NCOA2). © 2013 Wiley Periodicals, Inc.